INTEGRATED APPROACH AS THE BASIS FOR THE DEVELOPMENT OF COHERENT SPEECH OF FOREIGN LANGUAGE STUDENTS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article talks about teaching Russian to foreign students within the framework of international cooperation between Russian universities and foreign partners. Of great importance for the effectiveness of the process is the creation of an educational environment that allows for high quality educational services and the successful implementation of educational programs. A definition is given of the phenomenon of “educational environment”, which is one of the leading factors in personal development, provides the opportunity for young people to identify themselves in society, satisfy their own learning needs, and perceive education as a personal value. The author highlights the work experience of YSU teachers. I. A. Bunin on teaching Russian to Chinese students. The author considers the process of teaching foreign students more broadly than just teaching a non-native language, since the Russian language in this sense acts not just as an academic discipline, but also as a means of educational and cognitive activity and a means of communication. The article lists the difficulties that Chinese students encounter when mastering the norms of Russian spelling and grammar. The author highlights the basic principles of methodological work implemented in the course of teaching Russian as a foreign language (consciousness, functionality, consistency and communication). Of particular importance is the principle of co-teaching the language and culture of the people of the country of the language being studied. The internship program for Chinese students at the university, in addition to teaching the Russian language, includes a detailed acquaintance of students with the historical and cultural heritage of the city and its surroundings. The author summarizes that studying the Russian language in the educational environment of the Yelets region, in addition to obtaining linguistic and cultural knowledge and improving speech skills, contributes to the development of students' national self-awareness and cultural identification; the ability to compare fragments of cultural reality. The uniqueness of the historical and cultural heritage of the ancient city of Yelets and its surrounding area strengthens students’ motivation to study the culture and history of Russia and develops cognitive and research interest.